Water scarcity and challenges for smallholder agriculture - Giordano, Meredith A.; Barron, Jennie; Ünver, Olcay (Elsevier, 2019)
Water availability for agriculture will become a growing constraint in areas already under environmental and social stress due to population growth, development and climatic variability. This limits the potential for expanding irrigated areas and for sustainable intensification, and compromises the ability of smallholder farmers to cater to the increased demand for food. This chapter assesses the key global challenges to water availability and how increasing scarcity and competition for water resources are affecting agricultural productivity, especially that of smallholder producers in Asia and Africa. It further analyzes emerging water management practices that can be sustainably adapted to the needs of smallholder farmers. We provide evidence of the economic viability and potential to improve farmers’ income from such solutions. The opportunity for scaling up high-impact solutions is also assessed against available empirical evidence. Sustainable Food and Agriculture: An Integrated Approach is the first book to look at the imminent threats to sustainable food security through a cross-sectoral lens. As the world faces food supply challenges posed by the declining growth rate of agricultural productivity, accelerated deterioration of quantity and quality of natural resources that underpin agricultural production, climate change, and hunger, poverty and malnutrition, a multi-faced understanding is key to identifying practical solutions. This book gives stakeholders a common vision, concept and methods that are based on proven and widely agreed strategies for continuous improvement in sustainability at different scales.